The Improvement of Early Reading Ability Based Multiple Intelligences - Edwita, I Wayan Widiana, Arita Marini (International Journal of Advanced Science and Technology, 2020)
This research aimed to receive information regarding the method of improvement of early reading ability based on multiple intelligences of the lower grades’ students in the elementary school. The research was conducted from July to November, the first semester of 2013, was held in SDN 05 Pagi Jati Pulo Gadung Jakarta Timur, by using the action research method. The action research was conducted in two cycles. On each cycle consist of four phases; planning, action, observation, and reflection. Data collection was conducted through observation, assessment, and video recording. Data analysis was conducted by using a qualitative data analyzing. The reading tests consist of pre-test as the based for planning the intervention action. The following reading test conducted at the end of each cycle, in order to evaluate the effect of intervention action. The reading ability improvement was observed through the learning process and the reading tests on the end of the cycle. The process learning of reading based on the multiple-intelligences have three kinds of intelligences, the musical intelligence, visual intelligence, and kinesthetic intelligence. The research showed the reading ability of the first grade students in the elementary school have improved after using the multiple-intelligences learning. In conclusion, the research showed a significant improvement in student reading ability.